Aortic flow dynamics and stiffness in Loeys–Dietz syndrome patients: a comparison with healthy volunteers and Marfan syndrome patients. (9th June 2021) - Ruiz-Muñoz, Aroa; Guala, Andrea; Rodriguez-Palomares, Jose; Dux-Santoy, Lydia; Servato, Luz; Lopez-Sainz, Angela; La Mura, Lucia; Granato, Chiara; Limeres, Javier; Gonzalez-Alujas, Teresa; Galián-Gay, Laura; Gutiérrez, Laura; et al.
Abstract: Aims: To assess aortic flow and stiffness in patients with Loeys–Dietz syndrome (LDS) by 4D flow and cine cardiovascular magnetic resonance (CMR) and compare the results with those of healthy volunteers (HV) and Marfan syndrome (MFS) patients. Methods and results: Twenty-one LDS and 44 MFS patients with no previous aortic dissection or surgery and 35 HV underwent non-contrast-enhanced 4D flow CMR. In-plane rotational flow (IRF), systolic flow reversal ratio (SFRR), and aortic diameters were obtained at 20 planes from the ascending (AAo) to the proximal descending aorta (DAo). IRF and SFRR were also quantified for aortic regions (proximal and distal AAo, arch and proximal DAo). Peak-systolic wall shear stress (WSS) maps were also estimated. Aortic stiffness was quantified using pulse wave velocity (PWV) and proximal AAo longitudinal strain. Compared to HV, LDS patients had lower rotational flow at the distal AAo ( P  = 0.002), arch ( P  = 0.002), and proximal DAo ( P  < 0.001) even after adjustment for age, stroke volume, and local diameter. LDS patients had higher SFRR in the proximal DAo compared to both HV ( P  = 0.024) and MFS patients ( P  = 0.015), even after adjustment for age and local diameter. Axial and circumferential WSS in LDS patients were lower than in HV. AAo circumferential WSS was lower in LDS compared to MFS patients. AAo and DAo PWV and proximal AAo longitudinal strain revealed stiffer aortas in LDS patients compared to HV ( P  = 0.007, 0.005, and 0.029, respectively) but no differences vs. MFS patients. Conclusion: Greater aortic stiffness as well as impaired IRF and WSS were present in LDS patients compared to HV. Conversely, similar aortic stiffness and overlapping aortic flow features were found in Loeys–Dietz and Marfan patients.